Correlation Between Cardiovascular Endurance and Changes in Blood Pressure in Employees of Universitas Swadaya Gunung Jati, Cirebon, Indonesia - Ajeng Sanitaquin; Kati Sriwiyati; Sherly Cancerita (GHMJ (Global Health Management Journal), 2026)
Background: Blood pressure is the force exerted by blood on the walls of blood vessels and depends on cardiac output and peripheral resistance. Blood pressure is influenced by various factors, one of which is cardiovascular endurance. Optimal cardiovascular endurance helps maintain blood pressure at normal levels, thereby decreasing the risk of high blood pressure and cardiovascular disease. Aims: To determine cardiovascular endurance and blood pressure changes before and after performing the Harvard step test and to analyze the correlation between cardiovascular endurance and blood pressure changes in employees of Universitas Swadaya Gunung Jati, Cirebon, Indonesia. Methods: This study was a quantitative analytical observational type with a cross-sectional method involving 77 employees who are not registered as teaching lecturers who met the inclusion and exclusion criteria. This study was conducted by collecting primary data in the form of blood pressure measurement, Harvard step test treatment and pulse rate measurement. The data was then analyzed statistically using a Spearman’s hypothesis test.   Results: The majority of respondents were ≤40 years old (55.8%), male (64.9%), had a habit of smoking (55.8%), and abnormal HRR (83.1%). After conducting the Spearman test, p-value = 0.727; r = -0.041 for systolic and p-value = 0.314; r = -0.116 for diastolic. The correlation coefficient indicates a very weak negative correlation between cardiovascular endurance and blood pressure changes in employees of Universitas Swadaya Gunung Jati, Cirebon, Indonesia. Conclusion: There is no significant correlation between cardiovascular endurance and changes in blood pressure. Cardiovascular endurance showed a significant negative correlation with blood pressure, although other factors such as age, gender, physical activity, and smoking also play a role.